Livestock produce and their disposal pattern in Ladakh region of Jammu and Kashmir - AKAND, AFZAL HOQUE; SINGH, B P; CHANDER, MAHESH; AHMED, N (The Indian Journal of Animal Sciences, 2019)
This study was carried out in a sample of 120 livestock farmers selected from four blocks belonging to two districts of Ladakh region in Jammu and Kashmir to ascertain the role played by livestock in terms of their produce, viz. milk, wool/fibre, live animal and their consumption pattern including income derived out of these animals. The study revealed the average milk production/family/day was much higher in all blocks and varied from 5.83 to 9.46 litres/day/ family except in Nyoma where the corresponding figure was merely 0.56 and accordingly the consumption and sale volume. Sheep wool and goat fibre (Pashmina) were the dominant product of farmers belonging to Nyoma block with an average production of 42.97 and 39.86 kg/family/ year respectively. Although all farmers slaughtered small ruminant during winter for self consumption, it was higher in Nyoma (3.87 family/year) than other blocks (about 1/ family/year). Similar was the case with respect to number of small animal sold/family/year which was highest in Nyoma (15.02) as compared to other block that ranged between 2.23 to 3.36 on average value. The average income earned from all livestock sourced was recorded highest in Nyoma block, i.e. ` 196,550, whereas the same recorded for other blocks were between ` 39,269 to ` 67,393.66. The study reveals that the livestock production and their product consumption entirely depends on production system including the composition of the herd they maintain. Therefore, the developmental approaches should be local specific to address the local issues. Parallel emphasis may also be directed towards the value addition and marketing of livestock produces to influence both nutritional and economic impact among the livestock farmers.